Implementasi Etika Profesi Guru Pendidikan Agama Islam dalam Pembelajaran Online: Tinjauan Literatur terhadap Penerapan Kode Etik di Era Digital - Misran Misran; Humaida Humaida; Asaranum Sila Safitri; Latifah Nur Aprilyani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The rapid advancement of digital technology has significantly transformed educational practices, including Islamic Religious Education (PAI), which is increasingly conducted through online learning platforms. This transformation requires teachers not only to possess pedagogical competence but also to uphold professional ethics in digital learning environments. This study aims to analyze the implementation of professional ethics among PAI teachers in online learning through a literature review of teacher codes of ethics in the digital era. This research employs a qualitative approach using a library research method by examining relevant books, scholarly articles, and academic documents. The collected data were analyzed descriptively to identify key ethical principles applicable to online learning practices. The results indicate that the implementation of professional ethics in online PAI learning includes moral responsibility, professionalism, integrity, and the ethical use of digital media in a respectful and communicative manner. Furthermore, adherence to the teacher code of ethics plays a crucial role in maintaining the quality of learning and fostering Islamic values within digital environments. Therefore, strengthening ethical awareness and digital literacy is essential to support effective, responsible, and value-oriented learning in the digital era.